Management of patients with the atrophic variant of vulvar lichen sclerosus - Ekaterina V. Kolesnikova; Alexander V. Zharov; Grigory A. Penzhoyan; Natalia V. Mingaleva (IP Berlin A.V., 2022)
Aim.The objective is to optimize the diagnosis and management of the atrophic variant of the vulvar lichen sclerosus (LS). Materials and methods. We examined 58 female patients from 20 to 70 years old with the atrophic variant of the vulvar LS. The control group included 30 deemed healthy females 2070 years old. The atrophic variant of LS was diagnosed based on symptoms (dryness and discomfort in the vulva, superficial vulvodynia and dyspareunia, mild itching) and signs (marked atrophy of the external genitalia tissue up to aplasia of the labia minora and clitoris, vaginal stenosis, minimal hypopigmentation, absence of sclerosis). In addition, the following cytokines were measured in the peripheral blood of patients: interleukin (IL)-20, 23, 10, tumor necrosis factor-, and interferon-. The measurements were performed before and after immunotherapy with sodium deoxyribonucleate. Results. In all patients, there was a rapid shrinkage of the labia minora and clitoris, thinning and easy traumatization of the dermis and epidermis, contributing to secondary infection and synechiae formation up to complete vaginal occlusion. An increase in IL-23 (19.01 [18.0; 38.5] vs. 16.6 [12.98; 20.71] in the control group), 2.7-fold (p0.03) decrease in tumor necrosis factor-, interferon- and IL-20 are common for the atrophic variant of LS. The immunomodulatory and clinical efficacy of sodium deoxyribonucleate was demonstrated. Severe vulvodynia before treatment was noted in 29 (50%) patients and no patient (0%) after therapy; 44 (75.8%) patients reported complete reversal of superficial vulvodynia after treatment, and there were no patients without vulvodynia before treatment (0%). Mild itching before treatment was noted by 20 (40%) patients and 2 (3.4%) patients after treatment. Considering the cytokine levels, topical glucocorticoids in atrophic LS are inappropriate and can lead to atrophy and immunosuppression aggravation, contributing to the secondary infection. Conclusion. The observed differences in cytokine levels in patients with atrophic vulvar LS confirm the relevance of LS clinical classification by variants, support their use for LS diagnosis and immunotherapy efficacy control, and also suggest a differentiated approach to the treatment of different LS variants considering the effect of the drugs used on cytokine status.